2009
DOI: 10.1111/j.1365-2206.2008.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I can see parents being reluctant’: perceptions of parental involvement using child and family teams in schools

Abstract: The purpose of this study is to examine the attitudes beliefs, and perceptions of school and community personnel regarding parental involvement via the implementation of child and family team meetings. Interviews were conducted with 10 school and community personnel in a high school in a small county in the south‐eastern region of the USA. Several themes emerged from the data, including the definition of parental involvement, parental work and life circumstances, and parental esteem and position within schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Fully actualizing CFST's vision of family inclusion may require making schools' human resource policies more flexible for school-based nurses and social workers, as well as rewarding those who meet more often with families off campus and outside business hours. Building ongoing teams including all relevant agencies in the development and execution of a single plan may hinge on changes to state funding and regulations, as well as opportunities to address some families' distrust of health and social services (Taliaferro et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fully actualizing CFST's vision of family inclusion may require making schools' human resource policies more flexible for school-based nurses and social workers, as well as rewarding those who meet more often with families off campus and outside business hours. Building ongoing teams including all relevant agencies in the development and execution of a single plan may hinge on changes to state funding and regulations, as well as opportunities to address some families' distrust of health and social services (Taliaferro et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Although long used by some schools in other countries (e.g., Hayden, 2009), Child and Family and related teams are newer to US schools (Taliaferro, DeCuir-Gunby, & Allen-Eckard, 2009). They are also more radical than they may initially appear, in two respects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that the stress and fatigue involved in working long or non-standard hours, especially when such hours are not a result of personal choice, can alter parents' mood and energy levels making them less emotionally available for high-quality interactions with children (Menaghan, 1991;Repetti, 1994) and for educational involvement activities (Grolnick, Benjet, Kurowski, & Apostoleris, 1997). In other words, these parents may become so downtrodden by the time pressures imposed upon them that they cannot give their children the necessary attention to promote achievement (Taliaferro, DeCuir-Gunby, & Allen-Eckard, 2009). Levels of parental involvement in education may, in turn, exert an impact on child academic achievement.…”
Section: Parental Involvement In Children's Educationmentioning
confidence: 96%
“…Enhancing the positive school experiences of children including the academic achievement is a welldocumented fact (Taliaferro et al, 2009). Learning performance as well as personal and social growth of students is helped by their help (Sehee et al, 2010).…”
Section: Effect Of Involvement Of Parents With Their Childrenmentioning
confidence: 99%